Engineering Sugar Utilization and Microbial Tolerance toward Lignocellulose Conversion - Nieves, Lizbeth M.; Panyon, Larry A.; Wang, Xuan (Frontiers in Bioengineering and Biotechnology, 2015)
Production of fuels and chemicals through a fermentation-based manufacturing process that uses renewable feedstock such as lignocellulosic biomass is a desirable alternative to petrochemicals. Although it is still in its infancy, synthetic biology offers great potential to overcome the challenges associated with lignocellulose conversion. In this review, we will summarize the identification and optimization of synthetic biological parts used to enhance the utilization of lignocellulose-derived sugars and to increase the biocatalyst tolerance for lignocellulose-derived fermentation inhibitors. We will also discuss the ongoing efforts and future applications of synthetic integrated biological systems used to improve lignocellulose conversion.